1989
DOI: 10.1093/bja/62.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and Postoperative Pain

Abstract: We studied 20 otherwise healthy women undergoing lower abdominal surgery. Immediately after wound closure, while still anaesthetized, they received either electroacupuncture (EA) or no further treatment. They were allowed pethidine for postoperative analgesia by patient-controlled infusion pump. Signs of postoperative distress (pain, nausea, drowsiness) were evaluated after 2 and 6 h by visual analogue scale scores. The group receiving EA consumed half the quantity of pethidine as that used used by the no trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 3 publications
0
34
0
4
Order By: Relevance
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1, 2, 5) but not in the other two (3,4).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1, 2, 5) but not in the other two (3,4).…”
Section: Discussionmentioning
confidence: 93%
“…# Acta Anaesthesiologica Scandinavica 47 (2003) R EPORTS have differed as to the clinical value of acupuncture, since the method was introduced as an anaesthetic technique in China in 1958 (1)(2)(3)(4)(5). One factor contributing to difficulties associated with clinical studies on acupuncture is the technical problem regarding blinding (6).…”
Section: Accepted For Publication 20 March 2003mentioning
confidence: 99%
See 1 more Smart Citation
“…Bu etkiyi kapı-kontrol teorisi ile açıklayan ça-lışmalar vardır. [4][5][6][7] Endorfin, enkefalin, dinorfin gibi endojen opioid salınımı da akupunktur analjesine katkıda bulunabilir. Akupunkturda birçok uygulama tekniği bulunmaktadır.…”
Section: Discussionunclassified
“…In addition, pain stimulates the sympathetic nervous system and causes increases in the heart rate, blood pressure, sweat production, and endocrine hyperfunction, and delays the patient′s prognosis (Edwards, et al, 2007;Kumar&Wilson, 2007). To date, only a few studies have investigated the effects of acupuncture on postoperative pain and have shown conflicting results (Christensen, et al, 1989;Christensen, et al, 1993;Galloway, et al, 1984;Martelete&Fiori, 1985). A critical difference among these studies was the stimulation modality and the lack of a sham control.…”
Section: Effect Of High and Low Frequency Ea On Pain After Lower Abdomentioning
confidence: 99%